INTELLECTUAL PROPERTY AS AN ACCOUNTING OBJECT - Saverskyi, O. A.; Naumenko, V. L.; Falchiyan, M. O. (Science and Transport Progress, 2008)
The article deals with the main aspects of accounting of intellectual property in compliance with Ukrainian and international standards of the accounting. It considers the method suggested by I. Zhuravskaya as well as its efficiency under necessity of an enterprise to use the intellectual property object immediately after completion of its creation.